Exclusive Islam From The Perspective of Ibn Taymiyah - Siti Mahmudah Noorhayati; Ahmad Khoirul Fata (UIN Sunan Kalijaga Yogyakarta, 2017)
To build the idea of Islamic inclusiveness, Nurcholish Madjid made Ibn Taymiyah a reference. The definition of “Islam” as al-inqiyad, al-istislam, and al-ikhlash by Ibn Taymiyah became the foundation for Madjid to propagate the ideology of religious unity of the prophets, in the form of monotheism or submission only to Allah. But on the other hand there are many scholars who viewed the contrary, that Ibn Taymiyah was not an inclusive thinker. Instead he was the source of inspiration for the contemporary Islamic radicalism. This paper attempts to probe the religious ideas of Ibn Taymiyah. The focus of this paper is on the thought of Ibn Taymiyah on Islam and other religions, especially Judaism and Christianity. Research on some of his works showed that it is not quite right to conclude that Ibn Taymiyah was an inclusive thinker. There are, in fact, some of his ideas that seem to be inclusive as Madjid referred to. However, in-depth study on his thought showed that he had exclusive views on Islam. In addition to interpreting Islam linguistically, Ibn Taymiyah also considered that Islam brought by Prophet Muhammad is the true way of salvation. Meanwhile Judaism and Christianity have experienced deviations and therefore cannot guarantee the salvation of their adherents.[Dalam upaya mengkonstruk pemikiran Islam inklusifnya, Nurcholish Madjib merujuk pemikiran Ibnu Taymiyah sebaga landasan definisi sikap keislaman. Bagi Ibnu Taymiyah, definisi Islam ialah sikap tunduk/patuh (al inqiyad), memberikan keselamatan (al Istislam), dan keluhuran budi (al ikhlas). Corak pendefinisian ini juga dijadikan Nurcholis Madjid untukmempropaganda kesatuan ideology kenabian dalam bentuk kesatuan ketuhanan dan kepatuhan hanya pada Allah. Pada sisi yang lain, pandangan Nurcholish Madji ini jauh berbeda dengan para cendikiawan muslim yang lain. Posisi Ibnu Taymiyah terkait sikap keislaman dikategorikan sebagai pemikir ekslufisme dan fundamentalisme. Bahkan, tidak jarang dari mereka, mengatakan jika ajaran Ibnu Taymiyah menjadi sumber pemikiran radikal di era sekarang. Oleh karena itu, artikel ini akan mencoba untuk mengeksplorasi ide Ibnu Taymiyah secara holistik, khususnya sikap inklusif-eksklusif terhadap agama lain. Pada kesimpulannya, berdasarkan karya pribadinya, membuat konklusi Ibnu Taymiyah sebagai pemikir Islam-Inklusif tidaklah, sepenuhnya benar. Ada banyak fakta sikap Ibnu Taymiyah yang berbeda dari pemikiran inklusif. Sebab, kalau diteliti secara mendalam, pemaknaan linguistic terhadap kata Islam sendiri bagi Ibnu Taymiyah adalah kepasrahan dan penyelematan yang datang dari Nabi Muhammad SAW. Dia masih menganggap bahwa agama lain merupakan wujud deviasi dari ajaran Islam. Serta, ketundukan mereka tidak akan membawanya pada keselamatan nantinya.]